Dietary Vegetable Powders Modulate Immune Homeostasis and Intestinal Microbiota in Mice - Yixin Zou; Haifei Yu; Li Zhang; Zheng Ruan (Foods, 2021)
As the largest immune organ of the human body, the intestine also plays a vital role in nutrient digestion and absorption. Some vegetables are considered to have improvement effects on the intestine. This experiment explored the effects of freeze-dried asparagus, broccoli and cabbage powder on the intestinal immune homeostasis and microflora of mice. Thirty-two mice were divided into four groups (n = 8), including control group (fed normal diet), asparagus group (fed normal diet with 5% asparagus power), broccoli group (fed normal diet with 5% broccoli power) and cabbage group (fed normal diet with 5% cabbage power). The experiment lasted 21 days. The results showed that the serum immunoglobulin concentration (IgA and IgM) and intestinal cytokine content (like IFN-γ and TNF-α) were increased after vegetable powder supplement. The experiment also detected that vegetable powder supplementation changed intestinal flora and their metabolites (short-chain fatty acid), which showed that the abundance of Lachnospiraceae and Bacteroides were decreased, while the abundance of Firmicutes and Lactobacillus as well as propionic acid and butyric acid contents were increased. Together, these vegetable powders, especially cabbage, changed the intestinal immune response and microbial activity of mice.